Predlogi za spremembe Zakona o gospodarskih družbah - novela ZGD-1I - Kocbek, Marijan (Podjetje in delo, 2014)
The author discusses some of the proposals for the latest changes to the Slovenian Companies Act, the amendment ZGD-1I. The Ministry in charge of the amendment preparation gave a public call to professional audience to hand in proposals regarding the changes to the law. The main reason for the change in the law is the implementation of the new EU directives in the field of balance sheet and accounting rules, which combines the existing fourth and seventh Directive. In addition, the relatively extensive amendment will bring some other changes regarding the foundation and operation of companies, particularly in terms of increased efficiency in proceedings as well as towards greater protection of minority shareholders and creditors. The author specifically addresses some of the proposals relating to damage liability of the management and supervisory bodies and the operation of affiliated companies within the law of concern of companies.
Keywords: gospodarske družbe; management; odgovornost; pravna ureditev; računovodstvo; upravljanje; vodenje